2021
DOI: 10.1109/access.2021.3086111
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Koopman Model Predictive Control for Optimal Operation of High-Speed Trains

Abstract: Automatic train operation systems of high-speed trains are critical to guarantee operational safety, comfort, and parking accuracy. However, implementing optimal automatic operation control is challenging due to the train's uncertain dynamics and actuator saturation. To address this issue, this paper develops a data-driven Koopman model based predictive control method for automatic train operation systems. The proposed control scheme is designed within a data-driven framework. First, using operational data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Only one single study was found pertaining to this vehicle category, which was for an MPC application of a high-speed train whose linearized model was obtained via EDMD [49]. Remark 9 (Identified Gap in the Literature): For this vehicle class, we have not been able to find from the surveyed literature studies pertaining to trams, cable cars and roller coasters.…”
Section: G Railmentioning
confidence: 99%
“…Only one single study was found pertaining to this vehicle category, which was for an MPC application of a high-speed train whose linearized model was obtained via EDMD [49]. Remark 9 (Identified Gap in the Literature): For this vehicle class, we have not been able to find from the surveyed literature studies pertaining to trams, cable cars and roller coasters.…”
Section: G Railmentioning
confidence: 99%
“…In doing so, the ILC algorithm designed in [17] becomes feasible and it is able to ensure the convergence of the tracking process in the presence of time-varying adhesion dynamics between wheel and track via the definition of a new Composite Energy Function (CEF), without requiring the common assumption in ILC theory of globally Lipschitz property for the dynamic system. To face both uncertain dynamics and actuator saturation, an adaptive data-driven Koopman MPC strategy is introduced in [21] to solve the automatic train tracking control problem. Herein, firstly the Koopman operator theory is used to obtain an explicit linear dynamical train model that reflects train nonlinearities, thus resulting in a Koopman model involving an online adaptive mechanism able to cope with the changing dynamic characteristics; then MPC is designed under comfort and actuator constraints.…”
Section: A Related Workmentioning
confidence: 99%
“…Koopman operator is an infinite dimension data-driven linear operator, which can fully capture the nonlinear dynamics of the system [22], and provide a good practical value for the modelling of complex nonlinear systems. The vehicle operation data and Koopman operator is used to identify the linear dynamics model of urban rail vehicle [23]. For the dynamic system of urban rail vehicle, the observation function corresponding to each carriage is defined as…”
Section: Koopman Model Of Urban Rail Vehiclementioning
confidence: 99%